2010
DOI: 10.19030/jber.v8i10.768
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Portfolios For Different Holding Periods

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…This shows that depending on the increase in the financial literacy levels of the investors, the holding time of the stock is prolonged. These results support the work of Jack (Choi, & Mukherji, 2010;Chakrabarty et. al.…”
Section: Conclusion and Evaluationsupporting
confidence: 92%
See 1 more Smart Citation
“…This shows that depending on the increase in the financial literacy levels of the investors, the holding time of the stock is prolonged. These results support the work of Jack (Choi, & Mukherji, 2010;Chakrabarty et. al.…”
Section: Conclusion and Evaluationsupporting
confidence: 92%
“…Despite this, 580 survey data were used in the study to provide a better representation of the population. While creating the questionnaire questions, few studies in the literature were used (Choi & Mukherji, 2010;Estrada, 2014;Lyle & Wang, 2015;Karabay, 2018).…”
Section: Sample Size and Selectionmentioning
confidence: 99%
“…they converges to 0 when number of included observations tends to infinity. According to Choi and Mukherji (2010), supporters of time investment portfolio diversifications suggest a decrease of stock return volatility when comes to a certain increase of included observations. Cogneau and Zakamouline (2010) accept the fact that time period is one of the crucial in defining an optimal portfolio allocation.…”
Section: Testing Portfolio Sensitivity For Investment Period Lengthmentioning
confidence: 99%
“…The primary purpose of the subject research is to analyze hotel investment risk based on annual gross operating profit (GOP) of over 3,000 hotels during the course of six recent years, focusing on measuring hotel risk by using GOP profit margin, GOP per available room (GOPPAR), and relative standard deviation of GOP (GOP RSD). While previous research has acknowledged that having approximately 30 points of data regarding the holding period (HP) may be desired (Choi & Mukherji, 2010; Mukherji, 2003), recent research has shown a significant decrease in the HP (Poretti & Das, 2020). For example, Poretti and Das (2020) noted that the HP of hotels has been decreasing in recent years from approximately 15 years to approximately 5 to 8 years.…”
Section: Introductionmentioning
confidence: 99%